161k views
5 votes
Solve the equation 24= 6(-x - 3)

User PatrickT
by
4.6k points

1 Answer

6 votes

Answer:

X= -7

I LOVE LOVE LOVE LOVE EQUATIONS.

Explanation:

ALRIGHT!

1. 6*(-x)= -6x

2. 6*(-3)= -18

3. Now right in normal 24= -6x-18

4. Now keep the variables on one side and the numbers on the other and simplify it. And when keeping the variables on one side and the numbers on the other what ever you switch you must change it's expression. So if it's + you make it - and if it - you make it +. so 6x=-18-24= 6x=-42

5. Now simplify it. as a fraction. 6x = -42 = divide 6 on both sides now X= -7 6 6

User Kohi
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.